АДМИНИСТРАТИВНО-ПРАВОВЫЕ ФОРМЫ И МЕТОДЫ ОБЕСПЕЧЕНИЯ НАЦИОНАЛЬНОЙ БЕЗОПАСНОСТИ И ОБОРОНЫ ВООРУЖЕННЫХ СИЛ УКРАИНЫ - Нестеренко, Александр Владимирович (SUPREMANCE OF LAW, 2018)
The article draws attention to the relevance of improving the administrative and legal forms and methods of ensuring national security and defense by the Armed Forces of Ukraine in the context of reforming the Armed Forces of Ukraine and bringing their activities closer to NATO standards. The work comprehensively investigates the administrative and legal forms and methods of ensuring national security and defense by the Armed Forces of Ukraine. Theoretical and legal approaches to the definition of the concepts of "form" and "method", the allocation of their types and classificationare generalized and analyzed. The article analyzes the existing administrative and legal acts, regulating the administrative and legal forms and methods of ensuring the national security and defense of Ukraine by the Armed Forces of Ukraine. The terminological apparatus is improved; in particular, the essence of the concepts of administrative and legal forms and methods of ensuring the national security and defense of Ukraine by the Armed Forces of Ukraine is clarified. The types of administrative and legal forms and methods of ensuring the national security and defense of Ukraine by the Armed Forces of Ukraine are specified and classified.
Keywords: administrative-legal form; administrative-legal method; Armed Forces of Ukraine; national security; defense; ensuring national security